An approach to teaching the psychiatric interview - Timothy Hierlihy; Andrew Latus (BMC Medical Education)
Abstract The psychiatric interview serves as the cornerstone of psychiatric practice. It is therefore essential that we find effective ways of teaching students how to conduct a psychiatric interview. The present paper arises from two faculty members at Memorial University of Newfoundland and Labrador considering how to improve the quality of teaching of the psychiatric interview to preclerkship undergraduate medical students, before they begin the clinical portion of their training. The interview is taught in discrete pieces initially (e.g., discussing confidentiality, screening for suicidal ideation, taking a history for depressive disorders, etc.) before being assembled into a whole interview. The sessions are led by psychiatrists and residents who play the role of the patient. They use prewritten cases but can improvise to challenge or direct the students. Students receive real time feedback. The flexibility allows for students to repeat and vary their approach in response to feedback. Anonymous course evaluations showed improvement in student satisfaction with the new psychiatry clinical skills teaching. Prior to implementing the new approach student satisfaction was at 3.9/5. With the new method scores improved to 4.7/5 and 4.5/5 in the following two years. Clinical skills OSCE scores remained stable with modest improvement following implementation. The class average was 8.5 in the year prior to implementation and were 9.1, 8.6 and 8.8 in the years following. As a side benefit, the approach lent itself well to being delivered remotely so it continued to function well during the disruption resulting from COVID-19.